Application of Hmong Painting Patterns to Batik Motifs Design in Anshun, Guizhou, China - Lin, Panli; Sharudin, Sharul Azim Bin (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose/Background: The Hmong ethnic minority in Anshun, China has a rich cultural  heritage of embroidery handicrafts used in traditional rituals and festivities. This study aimed  to examine the cultural significance and creative applications of traditional Hmong embroidery  painting patterns.  Methods: A qualitative approach was used involving semi-structured interviews with Hmong  artisans in Anshun. Interviews explored cultural meanings of Hmong patterns and the process  of adapting them into batik motifs. Detailed notes were taken during the interviews and later  analyzed. Findings: These artisans offered profound insights into the cultural significance of Hmong  painting patterns and highlighted the process of applying these patterns to batik motifs. The  thematic analysis of the interview highlighted the significant role of Hmong painting in the  preservation of the cultural heritage of the Hmong community and the promotion of creative  expression among the members of this ethnic community.  Conclusions: Findings demonstrate the value of Hmong embroidery patterns for maintaining  cultural identity and enabling innovation among Hmong artisans. Adaptation of these patterns  promotes cultural preservation while supporting economic development in the community. Preservation of traditional handicraft methods among the Hmong is vital for passing on this  cultural heritage.
Keywords: Hmong painting; Anshun; Batik motifs; art; ethnic embroidery; community development